2021
DOI: 10.1016/j.sjbs.2021.04.093
|View full text |Cite
|
Sign up to set email alerts
|

E74-like factor 3 suppresses microRNA-485-5p transcription to trigger growth and metastasis of ovarian cancer cells with the involvement of CLDN4/Wnt/β-catenin axis

Abstract: Ovarian cancer (OC) is one of the most prevailing gynecological malignancies with high mortality rate, while E74 like ETS transcription factor 3 (ELF3) is reported to be associated with tumorigenesis. This work aims to analyze the role of ELF3 on the suppression of miR-485-5p transcription in OC. Expression of ELF3 in OC and its correlation with overall survival were predicted on a bioinformation system GEPIA. Then, the level of ELF3 in OC tissues and cells and in normal ones was evaluated. Binding relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Claudin-4 (CLND4) is directly targeted by miR-485-5p. Accordingly, miR-485-5p targeted CLDN4 for the inactivation of Wnt/β-catenin cascade in ovarian cancer cells (34). Overall, these findings suggested that ELF3 transcriptionally reduced miR-485-5p to potentiate CLDN4 expression.…”
Section: Wnt/β-catenin Signalingmentioning
confidence: 83%
“…Claudin-4 (CLND4) is directly targeted by miR-485-5p. Accordingly, miR-485-5p targeted CLDN4 for the inactivation of Wnt/β-catenin cascade in ovarian cancer cells (34). Overall, these findings suggested that ELF3 transcriptionally reduced miR-485-5p to potentiate CLDN4 expression.…”
Section: Wnt/β-catenin Signalingmentioning
confidence: 83%
“…62 Kuang et al pointed out that ELF3 promoted tumour growth and metastasis by inhibiting microRNA-485-5p. 63 Horie et al also suggested that elevated ELF3 expression level was linked to the tumour promotion traits in cancers. 64 Overall, our study provided the initial data regarding the potential mechanisms of CLDN4 contributing to the recurrence of MPE in advanced NSCLC, while further in-depth experiments were required to perform to validate its specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Kuang et al. pointed out that ELF3 promoted tumour growth and metastasis by inhibiting microRNA‐485‐5p 63 . Horie et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELF3 overexpression is reported to promote the pathogenesis of OC through the mTOR signaling pathway and induce cisplatin resistance in OCs (Liu et al , 2021 ). Furthermore, ELF3 is also known to promote OC cell growth and metastasis by inhibiting miR‐485‐5p transcription, which interferes with the CLDN4/Wnt/β‐catenin axis (Kuang & Li, 2021 ). A number of researchers continue to investigate the relationship between OC and ELF3.…”
Section: Introductionmentioning
confidence: 99%